2023
DOI: 10.1088/1742-6596/2459/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Micro-Electric Vehicle with Super Capacitor/Battery Hybrid Energy Storage System

Abstract: For the self-developed micro-electric vehicle (MEV), the supercapacitor/battery hybrid energy storage system (HESS) parameters were matched by analyzing the vehicle dynamic and economic constraints. The power distribution of HESS was realized by the fuzzy control strategy, and the entire vehicle model was also built to simulate the dynamic performance. The LCC model of MEV was established based on the comprehensive research of the life cycle cost (LCC). Quantitative comparisons and simulation results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The most important reason for this is that the price of a SC with the same energy capacity as a Li-ion battery is 275% higher [40]. However, studies have shown that the price difference between the lifecycle of SCs and Li-ion batteries is a false issue when the entire lifetime of the EV is considered [41][42][43]. Studies have shown that hybrid energy storage systems (HESS) with SCs increase the cost by about 25% but reduce the operating costs by 10% to 27% by extending the battery life [42].…”
Section: Introductionmentioning
confidence: 99%
“…The most important reason for this is that the price of a SC with the same energy capacity as a Li-ion battery is 275% higher [40]. However, studies have shown that the price difference between the lifecycle of SCs and Li-ion batteries is a false issue when the entire lifetime of the EV is considered [41][42][43]. Studies have shown that hybrid energy storage systems (HESS) with SCs increase the cost by about 25% but reduce the operating costs by 10% to 27% by extending the battery life [42].…”
Section: Introductionmentioning
confidence: 99%